Pengaruh Fluktuasi Harga Minyak Dunia Dan Kurs Rupiah Terhadap Profitabilitas Perusahaan Migas Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2025 - Farros Fadhlurrahim Yusri; Chaerani Nisa (JURNAL MANAJEMEN PENDIDIKAN, 2026)
The Effect of World Oil Price Fluctuations and the Rupiah Exchange on the Profitability of Oil and Gas Companies Listed on the Indonesia Stock Exchange for the 2020-2025 Period This study aims to analyze the influence of global oil prices and the rupiah exchange rate on the profitability of oil and gas companies. This study used quantitative methods using secondary data in the form of annual reports from oil and gas companies listed on the Indonesia Stock Exchange (IDX). Data analysis techniques included descriptive statistical analysis, classical assumption tests, multiple linear regression, the coefficient of determination (R2), and hypothesis testing using SPSS 25. The results showed that global oil prices had a significant partial effect on profitability, and the rupiah exchange rate also had a significant partial effect on profitability. The Adjusted R Square value was 0.579. This means that the variability of the global oil price and rupiah exchange rate variables only explained 57.9% of Return on Assets, while the remaining 42.1% was derived from external factors not included in this study.